Effects of nozzle types on mass diffusion mechanism of hydrogen multi-jets at supersonic combustion chamber. (December 2022) - Li, Z.; Leng, Jiaxuan; Abu-Hamdeh, Nidal H.; Abusorrah, Abdullah M.; Musa, Awad
Abstract: The fuel injection technique is the most effective procedure in the combustion chamber of supersonic/hypersonic vehicles. This work tries to explore the impact of the nozzle type on the fuel mixing of four multi-jet at a supersonic air stream of Mach = 4. Three different nozzles of rectangular (1:4), (1:16), and arc injector (1:16) are examined to obtain the efficient model for the injection system in combustor section. CFD method is used to simulate the flow and jet for the proposed nozzles inside the high-speed domain of the combustor. Our achieved results specify that increasing the jet injection along the direction of the airstream would significantly improve the mixing of hydrogen downstream of the injector and the rectangular nozzle (1:16) has the most efficient performance in this aspect. Strengths of circulation are improved by the concentrated injection system in which the fuel is injected through the limited nozzle.